The Institutional Dimension of City Branding (2022)
Since its origins, cities have had to strive to attract resources in order to guarantee its existence. To this end, a long journey has been walked from place promotion to place branding, which is conceptualized today as a process of urban governance. This doctoral dissertation intends to contribute to the academic debate around city branding through a theoretical dialogue among the research domains of city branding, urban governance, and institutional theory, by exploring the stakeholders´ participation in city branding within the urban governance context in which it takes place. This novel approach aims to strengthen city branding theoretical foundations, while enriching the discussion from a socio-cultural context different from that commonly studied by providing empirical evidence through a case study conducted in a Colombian Caribbean city, Barranquilla. The evidence suggest that city branding is the result of a multi-agency collaboration shaped by the institutional arrangement of the place, whose modes of governance define the stakeholders that participate in the process through institutional work. The local government’s role of promoter, enabler, or partner in city branding, depends on the type of power it holds in the institutional arrangement of the place. City branding does occur in places where local government exercises a dominant power, but co-production happens in an exclusive way or among those urban stakeholders that the local government, as promoter-enabler, allows to participate. The concept of City Branding Resilience is proposed with implications in the institutional, political, and temporal dimensions of city branding.